Current Trends in Collection Development Practices & Policies - Horava, Tony; Levine-Clark, Michael (Université d'Ottawa | University of Ottawa, 2016)
The purpose of this paper is to provide a snapshot of some major collections-related trends and issues in current academic libraries today. These include using collection development policies; demand-driven acquisition (DDA) models; big deals; using the collections budget; rationalizing legacy print collections; stewarding local digital collections; and demonstrating value.
Keywords: Trends; Practices; Academic libraries; Collection development; Survey; Policies